Impact of Insurance Status on Postoperative Recovery after Microsurgical Breast Reconstruction - Lu, Yi-Hsueh; Rothchild, Evan; Yan, Yufan; Mahajan, Lakshmi; Park, Michelle; Ricci, Joseph A. (Journal of Reconstructive Microsurgery, 2024)
Persistent disparities in breast reconstruction access have been widely documented, yet a significant research gap remains in understanding the impact of social determinants of health (SDOH) on postoperative outcomes and complications.A retrospective chart review was performed on all patients who underwent abdominal-based free-flap breast reconstruction between August 2018 and December 2022 at a racially, ethnically, and socioeconomically diverse urban academic institute with a historically underserved patient population. Patients were stratified by the public (Medicare and Medicaid) versus private insurance as a proxy for SDOH. Patient demographics, length of stay (LOS), timing in progression through postoperative recovery milestones, and complications were compared.A total of 162 patients were included, and 57% of patients had public insurance, with this group more likely to be Hispanic (odds ratio [OR] 2.7; p = 0.003) and Spanish-speaking (OR 3.4; p = 0.003). Privately insured patients were more likely to be non-Hispanic Black (OR 2.7; p = 0.006). Patients with public insurance had a higher rate of unplanned return to the operating room within 90 days and a higher incidence of complications, though not statistically significant. They also experienced a significantly longer LOS than privately insured patients (3.6 ± 1.0 vs. 3.0 ± 0.7 days; p < 0.0001). Logistic regression identified an LOS exceeding 3 days as independently associated with public insurance status (OR 3.0; p = 0.03), bilateral procedure (OR 5.6; p = 0.0007), preoperative functional-dependent status (OR 7.0; p = 0.04), and higher body mass index (BMI; OR 1.1; p = 0.03). Patients with public insurance were more likely to encounter delays in achieving recovery milestones.Public insurance status, serving as a proxy for a disadvantage in SDOH, is predictive of extended LOS and postoperative recovery delays following microsurgical breast reconstruction. This underscores the need for future quality improvement efforts to address and mitigate these disparities.
Keywords: microsurgical breast reconstruction; socioeconomic disparities; outcomes